A discussion of resilience and sustainability: Land use planning recovery from the Canterbury earthquake sequence, New Zealand. (December 2015) - Saunders, W.S.A.; Becker, J.S.
Abstract: The term 'resilience' is increasingly being used in a multitude of contexts. Seemingly the latest 'buzz' word, it can mean many things to many people, in many different situations. In the natural hazard context, the terms 'sustainable planning', and 'resilience planning' are now being used, often interchangeably. But from a natural hazard perspective, is a resilient community a sustainable one? In order to be sustainable, does a community need to be resilient? The purpose of this paper is to answer these two questions, and stimulate discussion on how the two terms are being used. The paper provides an overview of resilience and sustainability within a land use planning and natural hazard context, and discusses how they are interrelated. The New Zealand legislative requirements for resilience and sustainability are outlined, followed by the presentation of an example from the earthquake impacted city of Christchurch, New Zealand. This example outlines the planning response to the earthquakes, and the sustainable and resilient planning options being implemented. The discussion shows that a resilient community should also be a sustainable community, in order to meet legislative requirements, and – more importantly – to ensure the needs of future generations are met, economically, socially, culturally, and environmentally.